2016
DOI: 10.1161/hypertensionaha.116.07480
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment With an Erythropoietin Receptor Ligand Prevents Chronic Kidney Disease–Induced Enlargement of Myocardial Infarct Size

Abstract: We recently found that insufficient activation of Akt-mediated signaling underlies aggravation of reperfusion injury, leading to enlarged infarct size. 6 In addition to modified signal transduction, alteration in metabolism is possibly involved in CKD-induced increase in myocardial sensitivity to ischemia/ reperfusion (I/R) injury. Insulin resistance is a metabolic hallmark of uremia, 7,8 and Tamaki et al 9 showed that CKD induces substantial changes in metabolites and the number of mitochondria in skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Since EPO has been shown to be a cardioprotective molecule, it might be speculated that reduction in circulating EPO level contributes to infarct size enlargement by CKD. However, this possibility was not supported by the results of a study [26] conducted in parallel with the present study. In the second protocol of that study, we determined serum EPO levels in the same rat CKD model and sham-operated rats as those in the present study.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Since EPO has been shown to be a cardioprotective molecule, it might be speculated that reduction in circulating EPO level contributes to infarct size enlargement by CKD. However, this possibility was not supported by the results of a study [26] conducted in parallel with the present study. In the second protocol of that study, we determined serum EPO levels in the same rat CKD model and sham-operated rats as those in the present study.…”
Section: Discussioncontrasting
confidence: 95%
“…In fact, mitochondrial dysfunction [36] and down-regulated expression of the adiponectin receptor in the myocardium [35] were reported to be associated with increased myocardial injury by CKD. In our study conducted in parallel with this study [26], disturbed malate-aspartate shuttle in the myocardium in CKD was indicated by results of metabolome analysis. Relationships between mitochondrial dysfunction, impaired response of cytoprotective signaling, and duration and severity of renal dysfunction remain to be investigated.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…[11][12][13] Although CABG surgery has been reported with respect to low costs, superior outcomes, and particularly to short-term mortality, [14][15][16][17] multiple complications such as myocardial infarction (MI), myocardial ischemia, arrhythmias, stroke, and acute renal failure (ARF) are impossible to ignore and still perplex researchers and clinical doctors. 8,[18][19][20][21] To minimize the occurrence of postoperative complications, pre-and/or postoperative medicinal applications, such as phosphodiesterase (PDE) III inhibitors, have been primary strategies until now. [22][23][24] By reducing the inactivation of cyclic adenosine phosphate (cAMP) in cardiomyocytes, PDE III inhibitors enhance myocardial contractility and produce positive inotropic effects; 25,26 a higher concentration of cAMP results in contractility, increasing myocardial tissue and the vasodilatory effect on vascular smooth muscle.…”
Section: Introductionmentioning
confidence: 99%